2017
DOI: 10.1371/journal.pone.0187270
|View full text |Cite
|
Sign up to set email alerts
|

Experimental blunt chest trauma-induced myocardial inflammation and alteration of gap-junction protein connexin 43

Abstract: ObjectiveSevere blunt chest trauma in humans is associated with high mortality rates. Whereas lung tissue damage and lung inflammation after blunt chest trauma have extensively been investigated, the traumatic and posttraumatic effects on the heart remain poorly understood. Therefore, the purpose of this study was to define cardiac injury patterns in an experimental blunt chest trauma model in rats.MethodsExperimental blunt chest trauma was induced by a blast wave in rats, with subsequent analysis of its effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 48 publications
5
29
0
Order By: Relevance
“…An increased amount of deposited C3 cleavage products C3b/iC3b/C3c induces the second inflammatory phase after trauma, resulting in cardiac failure and death (52,53). In the present study, the expression of C5aR1 was slightly decreased in the lumen of the left ventricle after trauma in both polytrauma groups, which was also described previously after 72 h in an experimental polytrauma model in pigs and after 24 h in an experimental blunt chest trauma model in rats (54,55). The decreased expression of C5aR1 after trauma was associated with internalization of the receptor, triggered by C5a, which was further associated with CMs dysfunction and compromised cardiac function (25,56).…”
Section: Discussionsupporting
confidence: 88%
“…An increased amount of deposited C3 cleavage products C3b/iC3b/C3c induces the second inflammatory phase after trauma, resulting in cardiac failure and death (52,53). In the present study, the expression of C5aR1 was slightly decreased in the lumen of the left ventricle after trauma in both polytrauma groups, which was also described previously after 72 h in an experimental polytrauma model in pigs and after 24 h in an experimental blunt chest trauma model in rats (54,55). The decreased expression of C5aR1 after trauma was associated with internalization of the receptor, triggered by C5a, which was further associated with CMs dysfunction and compromised cardiac function (25,56).…”
Section: Discussionsupporting
confidence: 88%
“…Thereby, the conductance of Cx43 may be reduced by phosphorylation by the Ca 2+ -dependent protein kinase C (PKC) [80]. Moreover, in the present study, Cx43 was translocated from intercalated discs into the cytosol of the CMs (data not shown), which is in accordance to earlier studies in different trauma models, as well as in septic rodents and humans [18][19][20][21][22]. The translocation of the Cx43 was also demonstrated previously in ischemic as well as in nonischemic cardiac injury [81][82][83].…”
supporting
confidence: 92%
“…However, little is known about the effects of sepsis on the expression and distribution of other cardiac gap and tight junction proteins and cardiac structure. In previous experiments, our group showed that severe trauma affected cardiac structure and the localization of gap junction proteins [21,22]. Furthermore, we demonstrated that multiple trauma in pigs altered the expression of cardiac structure proteins, such as α-actinin and desmin.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Because of their cardio-depressive effects, pro-inflammatory cytokines and damage-associated molecular patterns (DAMPs) such as the high-mobility group box 1 (HMGB-1) protein and extracellular histones have been linked to post-traumatic cardiac dysfunction [6,[14][15][16]. A trend towards higher systemic concentrations of IL-6, plasma elastase, CD11b expression and soluble intercellular adhesion molecule 1 (s-ICAM-1) was found after femoral reaming, compared to non-reamed fracture stabilization [17].…”
Section: Introductionmentioning
confidence: 99%